Financial Capital, Human Capital, and the Transition to Self‐Employment: Evidence from Intergenerational Links - Dunn, Thomas; Holtz-Eakin, Douglas (Journal of Labor Economics, 2000)
We use data from the National Longitudinal Surveys to investigate the relative importance of family financial and human capital in the transition into self-employment. Specifically, we estimate the impacts of individual's own wealth and human capital and parental wealth and self-employment experience on the probability that an individual transits from wage-and-salary to self-employment. We find young men's own financial assets exert a statistically significant but quantitatively modest effect on the transition. In contrast, the parents' capital exerts a large influence. Parents' strongest effect runs, not through financial means, but rather through their own self-employment experience and business success. Copyright 2000 by University of Chicago Press.